INTER DISCIPLINARY MANAGEMENT OF MAXILLARY LATERAL INCISORS AGENESIS WITH IMPLANT PROSTHESES: A CASE REPORT. - MOHAMMAD KHURSHEED ALAM; ANAS IMRAN; HAMID H ENEZEI; FAZAL SHAHID; SHIFAT A NOWRIN; SHAIFULIZAN ABDUL RAHMAN (International Journal of Pharma and Bio Sciences, 2015)
Agenesis also called hypodontia is the most prevalent developmental dental anomaly in human. In order to treat a patient we need to identify the etiology of malocclusion and its accompanying factors. Three long-term management options exist: Lateralization of canine, Tooth borne restoration and Implant prostheses. This case report presents a 17-year-old Malaysian girl, congenitally missing upper lateral incisors having skeletal class III malocclusion complicated by mesially drifted canines and anterior crossbite. Fixed orthodontic alignment after space regaining followed by surgical placement of two single tooth implant for missing lateral incisors and provision of crown prostheses later on. Missing teeth were replaced by two single tooth implants, crossbite was resolved and normal overjet and overbite were established with coinciding midlines. Emphasis on early diagnosis with a team consultation followed by a timely planned and well executed inter-disciplinary treatment plan is the ultimate solution for such diverse cases.